A Comparison of Different A-, A-B-, and B-Site Incorporated in (Ba0.5Sr0.5)TiO3 on Photocatalytic Application. (28th December 2015) - Tubchareon, Tassanee; Klaysri, Rachan; Praserthdam, Piyasan
Abstract : The structural modification of Ba0.5 Sr0.5 TiO3 (BST) nanocatalyst was successfully synthesized via sol-gel process. The BST catalyst was modified by A-site (A-BST), A-B-site (A-B-BST), and B-site (B-BST) in order to investigate the effect of structurally modified BST catalyst for photocatalytic decolorization of methylene blue. The structurally modified BST catalysts can increase the nonradiation energy such as phonon energy compared to that of BST one. The partial incorporation of the A-BST catalyst was evidenced by the higher-ordered structure by increasing number of Ti 4+ ions and the lattice oxygen. The A-B-BST and A-BST catalysts were given more electron-transfer in the TiO6 than that of BST and B-BST catalysts, respectively. The A-B-BST catalyst promoted the oxidation of the lattice oxygen by holes capturing to form the chemisorbed oxygen, presenting the highest photobleaching activity of methylene blue. On the other hand, more oxygen vacancies recombination of BST catalyst compared to that of structurally modified BST catalysts presented the reduction of photocatalytic activity.